Association between eNOS Gene Polymorphism (T786C and VNTR) and Sickle Cell Disease Patients in Ghana - Antwi-Boasiako, C.; Dzudzor, B.; Doku, A.; et al. (Diseases, 2018)
Endothelial nitric oxide synthase (eNOS) variants have been found to be associated with several vascular disorders as well as the pathogenesis of sickle cell disease (SCD) complications such as vaso-occlusive crises (VOC). Studies on eNOS gene variants among SCD patients are rare in Ghana and several other African countries. The current study aimed to determine a possible association between variants of the eNOS gene (variable number of tandem repeats in intron 4 and T786C) in SCD complications among Ghanaian patients. This was a cross-sectional study involving 89 HbSS patients with complications and 46 HbSS patients without complications. Genomic DNA was extracted from leukocytes in the buffy coat and separated from collected whole blood samples of the study participants. PCR amplification, followed by restriction fragment length polymorphism (RFLP) was used to genotype T786C (rs2070744) variants. Variable number of tandem repeats (VNTR) in intron 4 was genotyped by PCR and direct electrophoresis. There was a significant difference in the genotype frequency of the T786C variant between HbSS patients with complications and those without complications (p = 0.0165). However, there was no significant difference in the VNTR intron 4 variant of the eNOS gene between patients with complications and those without complications (p > 0.05). The study shows an association between the eNOS gene variant (T786C) and complications in SCD.
Research Article
Keywords: eNOS; variants; sickle cell disease complications; allele; genotype